A Novel Deletion of IGF1 in a Patient With Idiopathic Short Stature Provides Insight Into IGF1 Haploinsufficiency - Batey, Lara (Endocrine Society, 2014)
CONTEXT: Short stature is a common reason for referral to pediatric endocrinology centers. Frequently, the underlying etiology of short stature is unknown, resulting in a diagnosis of idiopathic short stature. Rare genetic defects in the GH/IGF-1 axis have been found to cause short stature. OBJECTIVE: The objective of this study was to identify the genetic etiology of short stature in a patient with Idiopathic Short Stature and to review the clinical presentation of patients with genetic defects in IGF1, and specifically IGF-1 haploinsufficiency. DESIGN/SETTING/PARTICIPANTS: The index patient was evaluated at an academic medical center, and DNA was obtained from the proband and both parents. INTERVENTION: Genome-wide copy number analysis was performed in the proband with confirmatory quantitative PCR in the proband and his parents. MAIN OUTCOME MEASURE: We measured novel copy number variants (CNVs) thought to explain the patient's short stature. RESULTS: CNV analysis revealed that the proband carried a paternally inherited heterozygous IGF1 gene deletion. His phenotypic features are consistent with those found in previous case reports of IGF-1 deficiency. CONCLUSIONS: This study, as the first case of a complete heterozygous 1GF1 deletion, provides insight into the effects of true IGF-1 haploinsufficiency. Given the similarities in phenotype between the present proband and those previously described, it is highly likely that his IGF1 deletion is the cause for his short stature. Broadly, this study emphasizes how CNV analysis and other genetic sequencing techniques are evolving as an important tool to identify genetic causes underlying human disease, allowing for improved diagnosis and targeted treatment.